Castle in Siewierz. Preservation and revalorisation of the historic ruins - Rok, Artur (Protection of Cultural Heritage, 2018)
The conservation and restoration work was carried out on the ruins of Siewierz Castle between 2007 and 2010. The restoration and conservation work was made after detailed historical research conducted by Mr Artur Rok. Recomposition and revealment of the obliterated functional and spatial construction of the castle was the major aspect of the work as well as the conservation of stone and brick surface of the walls. The foundations of the Renaissance west and south wings of the castle were revealed and partly taken under conservation and reconstruction work. Tha main reconstruction work was carried out on the south walls of the castle which were badly damaged before the Second World War. The purpose of the work was purely technical and it led to show the image of the south part of the castle despite the fact that the highest tier was not reconstructed in order to maintain the appearance of ruin. The courtyard of the castle was arranged to feature the foundation of 13th century bergfried ( defensive tower) and the keep which is now open to visitors. Also the draw bridge was reconstructed which is not very common action in castles restoration in Poland. The restoration work in The Castle of Siewierz was conducted according to the rules of Venice Charter and Historican Ruins Protection Charter in order to maintain the uttermost authenticity of the castle.